Double purse‐string suture surgical wound closure after excision of nipple adenoma of the breast: A case report. Issue 5 (20th May 2022) - Bimpa, Kanelina; Charitou, Theodosia; Ziogas, Apostolos C.; Kantounis, Konstantinos; Xydias, Emmanouil; Bobos, Mattheos; Tsakos, Elias
Abstract: We present a rare case of nipple adenoma in a 53‐year‐old Caucasian woman. The lesion presented with a hemorrhagic nipple surface and was treated with wide surgical excision of the nipple and part of the surrounding areola and with a double purse‐string surgical closure of the remaining areolar area. This technique was considered safe and effective and aimed to reconstruct the nipple area, thus providing the patient with an acceptable aesthetic result. Double purse‐string surgical closure is proposed as a unique and straightforward, oncologically safe surgical procedure. This technique combines complete removal of the nipple adenoma, preservation of the remaining areola, minimization of skin flattening at the reconstructed area, improvement of the long‐term aesthetic result, and provision of a satisfactory surgical option for the patient. Abstract : Nipple adenoma is a rare, benign pathology that requires adequate excision and satisfactory surgical reconstruction. Our excision and double purse‐string suture method covered both requirements, forgoing necessitation of special training of the surgeon or expensive equipment, thus rendering it a simple, safe, and effective treatment option.